Persepsi Mahasiswa PGSD UKI Toraja terkait STEAM - Trivena Trivena; Weryanti Laen Langi' (Edumaspul: Jurnal Pendidikan, 2021)
This study aims to identify the perceptions of primary school teacher education students regarding STEAM. The type of research used in research is a qualitative-descriptive type of research. A questionnaire, consisting of 4 question items with multiple-choice answers and 48 statement items using a Likert scale. The collected data was transmitted in the form of questionnaire data to 100 students in the fifth semester of the Primary School Teacher Education UKI Toraja. The researcher then analyzed the data that had been collected. The results showed that, on average, students heard the term STEAM for the first time and only knew courses in the field of STEAM separately. The perception of the students towards STEAM regarding attitudes, opinions, and the environment is good. The students' motivation and belief to take courses in the STEAM area are already visible. The students are also very interested in studying STEAM courses and do not find these courses too difficult. The students also agree that the knowledge acquired in STEAM can help in developing a future career as a teacher. From an environmental point of view, however, the student's perception is positive that the curriculum, the facilities, the parents/relatives, and the lecturers strongly support STEAM learning.